Surface roughness after drilling of laminated chipboard - Szwajka, Krzysztof (Advances in Mechanical and Materials Engineering, 2015)
In this study the eighteen tests of tool durability for different values of the analyzed cutting parameters were carried out. Based on the results of investigations, the influence of selected cutting parameters on the machined surface quality was determined. Mathematical models based on analysis of variance (ANOVA), allowing to estimate the surface quality in the cutting process were proposed.